Analisis faktor-faktor yang mempengaruhi minat generasi Z untuk berinvestasi di pasar modal - Lara, Gita; Syaipudin, Usep; Widiyanti, Ade (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Researchers want to achieve the goal of knowing the factors that influence the interest of Generation Z to invest in the Indonesian capital market. What the researcher will examine is the impact of investment knowledge, returns, and risk preferences on investment interest in the Indonesian capital market. In addition, this research also examines the impact of indicators of investment knowledge including capital market seminars, capital market communities, capital market schools, and capital market courses on investment interest in the Indonesian capital market. The researcher used the Partial Least Square (PLS) SEM analysis technique with SmartPLS version 3.2.9 software. This type of research data uses primary data by distributing questionnaires. Meanwhile, the sampling technique used purposive sampling with a total of 190 respondents. The findings from the research state that investment knowledge and return have an impact on investment interest, risk preferences have no impact on investment interest. Another result of this study, testing the type of investment knowledge states that capital market schools have the greatest impacton investment interest.